ANALISIS TINGKAT EFEKTIVITAS PAJAK DAERAH SEBAGAI SUMBER PENDAPATAN ASLI DAERAH KOTA PONTIANAK - B61110033, SRI HANDOKO P, SE (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACTAnalysis of the Effectiveness of Local Tax Revenue Sources of PontianakTo determine and analyze the effectiveness of local taxes and determine the factors that affect local tax revenues Pontianak. The research method used is descriptive method. The technique used in this research is a comparative study, which is a descriptive research techniques seeking fundamental answers about the cause-and-effect by analyzing the factors that cause the occurrence or occurrence of a particular phenomenon.The types of data used in this study is a secondary data in the form of local income statements in the period of 5 years from the year 2007 to 2011 were obtained from the Central Bureau of Statistics and West Kalimantan Regional Revenue Office of Pontianak and the results of previous studies.The result is the ratio of the effectiveness of local tax revenue in 2007 was 100.15%, in 2008 was 99.18%, in 2009 was 102.49%, in 2010 was 103.45% and in 2011 was 113.68%, while the value of the local tax contribution to the native perndapaan reached 68.75%.Keywords: Revenue, Regional Tax